Quality indicators of colonoscopy care: a qualitative study from the perspectives of colonoscopy participants and nurses - Wenwen Cai; Xingxing Zhang; Yanxia Luo; Minshan Ye; Yu Guo; Weiqing Ruan (BMC, 2022)
Abstract Background Quality of care in colonoscopy is closely related to colonoscopy participants and the nursing workforce in endoscopy-related settings. However, limited data are available on the evaluations and recommendations regarding quality indicators for nursing care by these two groups. Therefore, the aim of this study was to explore the standards and requirements of quality of care in colonoscopy from the perspectives of patients and nurses. Method With a descriptive qualitative study, semi-structured interviews were conducted between November 2021 and January 2022 with colonoscopy participants (P = 11) and nursing workforce (N = 7) in the endoscopy unit in a tertiary hospital. The interviews were analyzed using a thematic analysis. Results Nine major themes emerged according to the structure, process, and outcome care quality model: workforce structure, quality requirements, unit facilities, nursing tools, nursing quality control systems, dynamic assessment and intervention, pre-examination care, strengthening education, and colonoscopy outcomes. Conclusion The indicator of quality of colonoscopy care should be used to assess and improve current practices to ensure a more direct and sustained impact of colonoscopy care. This study highlights the importance of nurse managers valuing the opinions and reflections of people involved in colonoscopy to improve the quality of colonoscopy care.